THE INFLUENCE OF ORGANIZATIONAL CULTURE CHARACTERISTICS, LOCUS OF CONTROL AND WORK DISCIPLINE ON TEACHER PERFORMANCE IN SEVERAL HIGH SCHOOL IN LHOKSEUMAWE CITY - Nahda Sri Wahyuni; Likdanawati; Aiyub Yahya; Khairawati (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Organizational Culture Characteristics, Locus of Control, and Work Discipline on Teacher Performance partially and simultaneously in several Senior High Schools (SMA) in Lhokseumawe City. This study uses a quantitative approach with a survey method and an instrument in the form of a closed questionnaire. The research sample consisted of 155 respondents who were active teachers from several senior high schools in Lhokseumawe City. The data analysis technique used was multiple linear regression with classical assumption testing, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination (R²). The results showed that partially, Organizational Culture Characteristics and Work Discipline had a positive and significant effect on Teacher Performance. While Locus of Control did not have a significant effect on Teacher Performance. Simultaneously, the three independent variables had a significant effect on Teacher Performance. The coefficient of determination (R²) value of 0.220 indicates that 22% of the variation in teacher performance can be explained by these three variables, while the remaining 78% is explained by other factors outside this research model. This research provides theoretical implications for strengthening organizational behavior models in educational settings, as well as managerial implications for developing organizational culture and improving teacher work discipline. Limitations of this research include its narrow scope, limited number of variables, and purely quantitative approach.